Russia and East Asia informal and gradual integration - Akaha, Tsuneo 1949- (Routledge contemporary Russia and Eastern Europe series, 2014)
"Russia has generally been neglected in the academic and policy discourse on regional integration in East Asia. This book fills this gap, with particular attention to the role of Pacific Russia in the deepening regional integration in East Asia. It examines the increasingly diverse foreign policy interests of Russia related to emerging economic and political realities of the world, and Russia's potential role in the regional integration in East Asia. Topics discussed include Russian strategic interests and security policy in East Asia generally, Russia's bilateral relations with China, Japan, and the Korean Peninsula, opportunities and challenges energy and immigration presents for Russia and its engagement with East Asia, and Russia's present and future roles in regional integration in East Asia".